Glutathione‐stabilized Fe3O4 nanoparticles as the sorbent for magnetic solid‐phase extraction of diazepam and sertraline from urine samples through quantitation via high‐performance liquid chromatography. Issue 6 (19th November 2020) - Ghani, Milad; Zayeri, Zahra; Maleki, Behrooz
Abstract: The synthesis and application of glutathione‐coated magnetic nanocomposite were introduced with the purpose of developing a stable, cheap, operationally convenient, simple, fast, sensitive, and selective device for the microextraction of diazepam and sertraline for the first time. The prepared glutathione@Fe3 O4 nanocomposite was used as the sorbent in the form of magnetic solid‐phase extraction. Afterward, the extracted analytes were desorbed by organic solvent and analyzed by high‐performance liquid chromatography‐ultraviolet detection. Several influential variables such as desorption time, desorption volume, sample pH, extraction time, and sorbent amount were screened through Plackett–Burman design and then optimized via Box–Behnken design. The obtained results showed that the above‐mentioned method enjoys a good linear range (0.2–500 μg/L) with the coefficient of determination higher than 0.9927, low limits of determination (0.07–0.24 μg/L), acceptable limits of quantification (0.22–0.93 μg/L), good enrichment factors (128 and 153), and good spiking recoveries (95–105%) for diazepam and sertraline under the obtained optimized condition. Analyzing the real samples results in the confirmation of the presented method and it can be applied for the analysis of various organic compounds in biological samples.